Sustaining Competitive Advantage Through Corporate Environmental Performance. (31st August 2016) - Yadav, Prayag Lal; Han, Seung Hun; Kim, Hohyun
Abstract: This research investigates the relationship between a firm's environmental efforts and the sustainability of its competitive advantage by analyzing the effects of change in firm environmental performance on the persistence of profitability growth. We find that environmental resources allow a firm with superior financial performance to sustain its competitive advantage, and also complement the efforts of a poorly performing firm to hasten recovery from inferior financial performance. Our findings further indicate that firms attain such positive effects through enhanced profit margins resulting from improved environmental performance. Additionally, we observe that a corporate strategy of improving environmental performance demonstrates management's responsibility to maximize the shareholder wealth of a well‐performing firm. The results provide valuable insights to align environmental activities towards developing unique resources for sustaining the competitive advantage. The study provides an empirical support for creating economic value by benefiting the environment. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment